Interprofessional Practice and Education in Clinical Learning Environments: Frontlines Perspective. (October 2018) - Uhlig, Paul N.; Doll, Joy; Brandon, Kristy; Goodman, Christopher; Medado-Ramirez, Josephine; Barnes, Michael A.; Dolansky, Mary A.; Ratcliffe, Temple A.; Kornsawad, Kanapa; Raboin, W. Ellen; Hitzeman, Maggie; Brown, Jeffrey; et al.
Abstract : This Invited Commentary is written by coauthors working to implement and study new models of interprofessional practice and education in clinical learning environments. There are many definitions and models of collaborative care, but the essential element is a spirit of collaboration and shared learning among health professionals, patients, and family members. This work is challenging, yet the benefits are striking. Patients and family members feel seen, heard, and understood. Health care professionals are able to contribute and feel appreciated in satisfying ways. Learners feel included. Care interactions are richer and less hierarchical, and human dimensions are more central. A crucial insight is that collaborative care requires psychological safety, so that people feel safe to speak up, ask questions, and make suggestions. The most important transformation is actively engaging patients and families as true partners in care creation. A leveling occurs between patients, family members, and health professionals, resulting from closer connections, deeper understandings, and greater mutual appreciation. Leadership happens at all levels in collaborative care, requiring team-level capabilities that can be learned and modeled, including patience, curiosity, and sharing power. These abilities grow as teams work and learn together, and can be intentionally advanced by reconfiguring organizational structures and care routines to support collective team reflection. Collaborative care requires awareness and deliberate practice both individually and as a team together. Respectful work is required, and setbacks should be considered normal at first. Once people have experienced the benefits of collaborative care, most "never want to go back."